DIVERSIFICATION OF THE MANUFACTURING INDUSTRY IN THE REGIONS OF UZBEKISTAN - Mukhsimova Dilafruz , Hikmatullaevna (THE INNOVATION ECONOMY, 2025)
The article analyzes the level of diversification of industrial sectors in the regions of Uzbekistan. The study evaluates the level of diversification of manufacturing sectors using the Herfindahl-Hirschman index. The research emphasizes the necessity of diversifying the industry, implementing innovations, modernizing the education system, and supporting small businesses to strengthen regional economic growth. Proposals and recommendations have also been developed on the state of the manufacturing industry in the regions of Uzbekistan, the factors influencing it and the development of its diversification